A Review of Ignition Characteristics and Prediction Model of Combustor Under High-Altitude Conditions - Yuhui Zhu; Shaolin Wang; Kaixing Wang; Yushuai Liu; Cunxi Liu; Fuqiang Liu; Jinhu Yang; Yong Mu; Gang Xu (Energies)
High-altitude relight is a critical challenge for aero-engines, directly impacting the safety and emergency response capabilities of aircraft. This paper systematically reviews the physical mechanisms, key factors, and relevant prediction models of high-altitude relight, highlighting the detrimental effects of extreme conditions such as low pressure and temperature on fuel evaporation rates, flame propagation speeds, and turbulent combustion processes. A comprehensive overview of the current state of high-altitude relight research is presented, alongside recommendations for enhancing the ignition performance of aero-engines under extreme conditions. This paper focuses on the development of ignition prediction models, including early empirical and semi-empirical models, as well as physics-based models for turbulent flame propagation and flame kernel tracking, assessing their applicability in high-altitude relight scenarios. Although flame kernel tracking has shown satisfactory performance in predicting ignition probability, it still overly relies on manually set parameters and lacks precise descriptions of the physical processes of flame kernel generation. Future studies on some topics, including refining flame kernel modeling, strengthening the integration of experimental data and numerical simulations, and exploring the incorporation of new ignition technologies, are needed, to further improve model reliability and predictive capability.